A role for interleukins in ochronosis in a chondrocyte in vitro model of alkaptonuria. Issue 7 (July 2016) - Mistry, J.; Jackson, D.; Bukhari, M.; Taylor, A.
Abstract Alkaptonuria is a rare autosomal recessive condition resulting from inability to breakdown homogentisic acid (HGA), an intermediate in tyrosine degradation. The condition has a triad of clinical features, the most damaging of which is ochronotic osteoarthropathy. HGA is elevated from birth, but pigmentation takes many years. We hypothesise that interleukins play a role in initiation and progression of ochronotic osteoarthropathy. C20/A4 cells were cultured and maintained in 9-cm petri dishes containing either HGA at 0.33 mM, a single interleukin (IL-1β, IL-6 or IL-10) at 1 ng/ml or a combination of HGA and a single interleukin. Statistical analysis of pigment deposits and cell viability was performed using analysis of variance with Newman-Keuls post-test. All cultures containing HGA showed a significant increase in pigment deposition compared to control and IL cultures alone. The cultures containing HGA and IL-6 showed a significant increase in pigment deposits compared to HGA alone. The cell viability counts across all cultures on day 10 demonstrated a significant decrease in cultures containing HGA compared to those which did not. There was no significant difference between cultures containing just HGA or those combined with an interleukin. This work demonstrates a role for cytokines present in the joint(s) in the pigmentation process, particularly IL-6, and that the presence of HGA in joint tissues appears more detrimental to chondrocytes than the presence of any of the interleukins found in response to joint injury, trauma and osteoarthritis (OA). This further supports the evidence that the arthropathy in alkaptonuria is much more severe and rapidly progressing.